Web-based Banking Services on E-Customer Satisfaction in Private Banking Sectors: A Cross-Sectional Study in Developing Economy - Most. Sadia Akter; Amin, Al-; Mohammad Rakibul Islam Bhuiyan; Tahmina Akter Poli; Rashed Hossain (Migration Letters, 2023)
The study intends to determine the web-based banking services that are impacting electronic customer satisfaction by the private banks in Bangladesh. Moreover, the study investigates the correlation between demographic information and web-based banking service quality and electronic customer satisfaction levels in Bangladeshi private banks. IBM SPSS Statistics 29.0 is used by researchers for analyzing the demographic values of the respondents. Conceptual research model analyzed by SmartPLS 4.0. The value of r square found in this study is 0.350, which indicates 35% of the variation in the outcome from independent variable to ECS. Assurance, e-learning, and service quality have a significant impact on achieving e-customer satisfaction in the private sector banks in Bangladesh that are supported by H1, H3, and H4. Bangladeshi private banking policymakers should introduce user-friendly and promising offerings to attract customers for faster adoption of web-based banking services by facilitating low-cost leadership, strong security, literacy, and awareness.